PENGARUH PRINSIP GAMIFICATION TERHADAP LOYALITAS MEREK DENGAN KETERLIBATAN PELANGGAN SEBAGAI VARIABEL INTERVENING (Studi pada Pengguna Lazada di Kota Semarang) - Azra Rafi Nur Asy'ari; I Made Sukresna (Diponegoro Journal of Management, 2023)
ABSTRACT E-commerce competition in Indonesia has forced e-commerce companies to create new strategies in order to maintain consumer loyalty. Gamification is believed to have a strong influence on being able to attract and engage consumers so that they are loyal to an e-commerce This study aims to determine the influence of gamification principles on customer engagement in brand loyalty. The sample used in this study amounted to 205 respondents and was selected by purposive sampling. The method used in data collection is a questionnaire. The data obtained from the results of the questionnaire were then processed and analyzed using the Structural Equation Model (SEM) technique using the AMOS software tool. The results of this study indicate that the principles of gamification consisting of social interaction, sense of control, goals, rewards, and prompts have a positive and significant impact on customer engagement, progress tracking has a negative impact on customer engagement, and customer engagement has a positive and significant impact on brand loyalty